The spectrum of the 2+1-dimensional gauge Ising model - Agostini, Valentina; Carlino, Gianpaolo; Caselle, M.; Hasenbusch, Martin (Nuclear physics. B, Particle physics, 1997)
We present a high precision Monte Carlo study of the spectrum of the Z2 gauge theory in 2 + 1 dimensions in the strong coupling phase. Using state-of-the-art Monte Carlo techniques we are able to accurately determine up to three masses in a single channel. We compare our results with the strong coupling expansion for the lightest mass and with results for the universal ratio σ/m2 determined for the φ4 theory. Finally the whole spectrum is compared with that obtained from the Isgur-Paton flux-tube model and the spectrum of the 2 + 1-dimensional SU(2) gauge theory. A remarkable agreement between the Ising and SU(2) spectra (except for the lowest mass state) is found.